Challenges of Implementing Knowledge Management Practices in Nepalese Financial Institutions - Khanal, Lekhanath; Mathur, S.P. (Nepal Journal of Multidisciplinary Research, 2020)
Knowledge management (KM) is the research field that still faces some lack of cumulative theoretical development and empirical studies. Despite several opportunities, one faces many challenges to explore these concepts and their implementation at organizational level. The main objective of this study was to explore the challenges of implementing Knowledge Management practice in Nepalese financial institutions. A convergent-parallel mixed method research was designed to explore the prevailing challenges of KM implementation in banking and financial sector in Nepal. In this study, a sample of 385 respondents was selected randomly from four different types of financial institutions of Kathmandu, Nepal. Quantitative as well as Qualitative analysis was carried out to draw the conclusion. This study identified major challenges faced by Nepalese financial institutions and the ways to resolve them and concluded that knowledge management as a practice and behavior could be the most influential strategy in banking and financial sector if opportunities were exploited eradicating the challenges properly.